2017
DOI: 10.1111/nbu.12281
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, epigenetics and health through life

Abstract: Epigenetics describe heritable changes to the genome without changes to the DNA sequence itself. Epigenetic marks include DNA methylation and histone modifications, and epigenetic molecules include microRNAs. Epigenetic mechanisms modulate gene expression and so regulate many cellular processes such as cell proliferation and cell death. As a consequence, changes to the epigenome may have consequences for the function of cells, tissues and organs and may modify the risk of developing disease. Epigenetic marks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 103 publications
(190 reference statements)
0
12
0
1
Order By: Relevance
“…One important epigenetic alteration is the methylation of DNA in and around promotor regions, which results in reduced or suppressed gene transcription and can be reversed or unmethylated. These epigenetic modifications are essential to normal biological functioning but may also be the result of environmental exposures including diet and bioactive compounds [ 37 ]. A growing body of literature has shown that both beneficial and harmful epigenetic changes can result from various dietary exposures [ 38 ].…”
Section: The Anatomy Of Gene–diet Interactionsmentioning
confidence: 99%
“…One important epigenetic alteration is the methylation of DNA in and around promotor regions, which results in reduced or suppressed gene transcription and can be reversed or unmethylated. These epigenetic modifications are essential to normal biological functioning but may also be the result of environmental exposures including diet and bioactive compounds [ 37 ]. A growing body of literature has shown that both beneficial and harmful epigenetic changes can result from various dietary exposures [ 38 ].…”
Section: The Anatomy Of Gene–diet Interactionsmentioning
confidence: 99%
“…That regulation is provided, in part, by the cell's epigenetic machinery. Epigenetics describes heritable changes to the genome without changes to the DNA sequence per se [1] .
In cancers and many other diseases, abnormal patterns of gene expression are associated with methylation of the promoter regions of specific genes leading to loss of function of the corresponding gene.
…”
Section: Epigenetics – the Basicsmentioning
confidence: 99%
“…This is an emerging field and much remains to be discovered but it appears that the chemically modified nucleosides in RNA play an important role in RNA homeostasis by regulating the amounts and activities of particular RNA species [4] . So far, little is known about whether, or how, environmental factors, such as diet, influence the epitranscriptomic landscape [1] but a potential link with obesity is discussed below.…”
Section: Iv) the Epitranscriptomementioning
confidence: 99%
“…It is the nutrition that interacts with each individual's genetic makeup to modulate mental health throughout the life course. The interactions between nutrition and genetics are mediated by epigenetic marks and molecules, which have a central role in the causal pathways between diet, genotype, and phenotype (Figure1) [8].…”
mentioning
confidence: 99%